Analysis of Instrument Quality in Measuring Mathematical Logical Thinking Ability - Yulia Pratiwi; Niki Pujarwati; Marlinawati Marlinawati; Agung Putra Wijaya; Chika Rahayu (Universitas Teknokrat Indonesia, 2026)
The ability to think logically in mathematics is a skill that must be developed through instruction. One strategy for developing this ability is the use of high-quality instruments. Therefore, this study aims to analyze the quality of a mathematical logical thinking ability test instrument in terms of its validity, reliability, difficulty index, and discriminating power using SPSS and Microsoft Excel. This research employed a quantitative method with an evaluative analysis approach. The subjects in this study were students of class VII.6 and VII.8 at SMPN 26 Bandarlampung. The instrument used was a descriptive test consisting of ten items, developed based on four indicators of logical thinking ability, namely the ability to interpret information, the ability to predict, the ability to solve problems, and the ability to draw conclusions. The results of this study indicate that: (1) the quality of the logical thinking ability test instrument meets the criteria for 100% validity; (2) the reliability of the logical thinking ability test instrument is 0.775, categorized as reliable; (3) the difficulty level analysis shows that nine items fall into the moderate category and one item falls into the easy category; (4) the discrimination power analysis shows that four items have good discriminating power and six items have fair discriminating power.